The South American Pacific and its integration with China and Asia - Torres González, Jaime (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The present work confronts the industrial policies followed by the South American nations with those of the Southeast Asian countries, and states that the influence of the Washington Consensus on the former allowed to disrupt their industrial development, while the type of economic development in Asia has been more successful, framed in recent decades in what is known as the Beijing Consensus. A comparative study is made of the evolution of different economic and social indicators of the South American nations, as well as of Malaysia, Thailand and Vietnam, using United Nations-Comtrade trade data and World Bank World Development Report 2015 indicators. It is found that the persistence of industrial policies and the link to international trade explain an important part of the Asian results. A recovery of these policies in South America could help to activate the economic dynamics offered by the export of natural resources.